Pengaruh Video Tiktok terhadap Keterampilan Menulis Teks Berita Siswa Kelas VII SMPN 13 Kota Bengkulu - Aisyah, Mutiara; Yanti, Nafri; Yulistio, Didi (UNIB Press, 2025)
This study aims to determine the effect of TikTok videos on the news text writing skills of class VII students of SMP Negeri 13 Bengkulu City. This study uses a quantitative approach and experimental method, comparing the posttest scores between groups that use print media and those given Tiktok videos after learning to write news texts. The population of this study were all class VII students of SMP Negeri 13 Bengkulu City with sampling using simple random sampling and purposive sampling techniques. A sample of 28 students from class VII C and class VII D was obtained. The data collection technique used a test technique with a research instrument in the form of an essay test. The data analysis technique used an independent two-sample t-test. The normality test was carried out using the Shapiro Wilk formula and the homogeneity test used the Fisher test formula. This is due to the advantages of this media that are able to present information visually and attractively, making it easier for students to understand the structure of the news. There are differences in the writing skill scores of students who were taught using TikTok videos and students who were taught using print media. The average value of the experimental class was 72.25 and the average value of the control class was 67.59. The influence of TikTok video media is also proven by the t-test which shows that , namely 8.65> 1.67. When viewed from Sig. (2-tailed) obtained from the t-test via SPSS, which is 0.00 <0.05, then is also rejected.